2008
DOI: 10.5206/eei.v18i2.7624
|View full text |Cite
|
Sign up to set email alerts
|

Compensating for Reading Difficulties:A Qualitative Investigation of University Students’ Experiencesof Influential Personal Characteristics

Abstract: This study involved a qualitative examination of the personal characteristics that university students saw as important in helping them to compensate for their reading difficulties at various stages of their education. The sample consisted of 10 undergraduate students or recent graduates who reported a significant history of reading difficulties. Data were collected using in-depth, open-ended interviews with each participant. These data were then analyzed using a form of whole text analysis and resulted in fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 33 publications
0
16
1
Order By: Relevance
“…This study supported the results of another qualitative analysis of Australian university students with dyslexia who reported developing compensation strategies, and hiding their disability (Tanner, 2009). Other qualitative studies have also demonstrated the importance of the compensation strategies utilized by postsecondary students with dyslexia (Corkett, Hein, & Parrila, 2008; Cowen, 1988). This research evidence using samples of postsecondary students with reading difficulties found that some participants could compensate for their disabilities, providing some information about potentially effective strategies.…”
mentioning
confidence: 98%
“…This study supported the results of another qualitative analysis of Australian university students with dyslexia who reported developing compensation strategies, and hiding their disability (Tanner, 2009). Other qualitative studies have also demonstrated the importance of the compensation strategies utilized by postsecondary students with dyslexia (Corkett, Hein, & Parrila, 2008; Cowen, 1988). This research evidence using samples of postsecondary students with reading difficulties found that some participants could compensate for their disabilities, providing some information about potentially effective strategies.…”
mentioning
confidence: 98%
“…Competence in one's abilities and future plans has been found to assist adults with RD during their education. In Corkett et al's (2008) study, adults with RD reported that believing in themselves kept them focused on their goals-it was not a matter of whether these adults would attend university, but a matter of when they would go.…”
Section: Multiple Indicators Of Resiliencementioning
confidence: 90%
“…The ability to develop positive relationships appears to be a key characteristic of successful adults with LD (Gerber et al, 1992). Building rapport with teachers and professors helped adults with RD gain educational accommodations and information they may not have otherwise garnered (Corkett et al, 2008). Some adults with LD experience successful social interactions (Gerber et al, 1992; Greenbaum et al, 1995), whereas others have problems developing and maintaining relationships (Goldberg et al, 2003; Hellendoorn & Ruijssenaars, 2000; Litner, Mann-Feder, & Guérard, 2005).…”
Section: Multiple Indicators Of Resiliencementioning
confidence: 99%
See 2 more Smart Citations